2021
DOI: 10.1002/bem.22348
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pulsed Electromagnetic Fields on Experimental Osteopenia in Rodents: A Systematic Review

Abstract: Osteoporosis leads to increased bone fragility and risk of fractures. Different strategies have been employed to reduce bone loss, including the use of a pulsed electromagnetic field (PEMF). Although many experimental studies have demonstrated the effect of PEMF on reduction of bone loss, the outcomes studied are varied and insufficient, and the quality of evidence is unknown. Therefore, the aim of this review was to assess the preclinical evidence on the effect of PEMF on bone loss. The existing challenges we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…A recent review showed positive effects of PEMFs in the treatment of osteoporosis in 23 out of 24 studies included in the study. In particular, PEMFs increase bone mineral mass and reduce symptoms related to osteoporosis [64].…”
Section: Osteopenia and Osteoporosismentioning
confidence: 99%
“…A recent review showed positive effects of PEMFs in the treatment of osteoporosis in 23 out of 24 studies included in the study. In particular, PEMFs increase bone mineral mass and reduce symptoms related to osteoporosis [64].…”
Section: Osteopenia and Osteoporosismentioning
confidence: 99%
“…In the experimental approach to this topic, a review paper from 2021 [46] identified a total of 24 viable studies with evaluated parameters from bone mineral density to biochemical analyses, and from histological/histomorhometric workups to CT scans. Of these, 23 showed a positive effect of PEMF on the parameter(s) evaluated in each case.…”
Section: Osteopeniamentioning
confidence: 99%
“…Moreover, they are small and easily fit in cages to perform PEMF stimulation. Their fast growth rate and accelerated bone metabolism also allow adequate assessment of the efficacy of treatment [35]. In iatrogenic osteotomies both large (such as dogs, sheep, goats, horses and nonhuman primates) and small sized (such as rats, mice and rabbits) animals can be selected.…”
Section: Animal Modelsmentioning
confidence: 99%